Orientalism and New musicology - Nikolić, Sanela (Array, 2019)
The aim of this paper is to outline the history of the concept of Orientalism in the field of New musicology and to point out that musicological discussions of Orientalism significantly changed disciplinary profile of musicology in the direction of interdisciplinary or contextual musicology. The area of Postcolonial studies has been recognized by New musicology as a possible starting point for theorizing the new issues related to the questions of music, race, ethnic and national otherness, and European colonialism. In 1991, with the publication of Ralph P. Locke’s text “Constructing the Oriental ‘Other’: Saint-Saëns’s Samson et Dalila” in Cambridge Opera Journal, the musicological research of the European professional music tradition from the aspects of postcolonial theories has been institutionalized and the concept of Orientalism has been introduced into the field of research objects of musicology. What is present as the common aspects of all musicological studies that address the issue of musical representations of the Orient are interdisciplinarity and contextuality. Contrary to the reduction of the complex Western European music practices to the idea of an autonomous work of music devoted to an aesthetic enjoyment, postcolonial musicology proposed poststructuralist analytical models of text and discourse and affirm the interest in the context of work of music. In that manner, musicology has been updated as a discipline that autocritically approaches Western European professional music practice by seeing it/ self as only one of the possible historical formations of culture/knowledge in which there are visible clusters, conflicts, and aspirations to present (Western) European capitalist patriarchal politics as a universal economic, political and cultural power.